2022
DOI: 10.1186/s40035-022-00313-1
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of furin in neurodegenerative and neuropsychiatric diseases

Abstract: Furin is an important mammalian proprotein convertase that catalyzes the proteolytic maturation of a variety of prohormones and proproteins in the secretory pathway. In the brain, the substrates of furin include the proproteins of growth factors, receptors and enzymes. Emerging evidence, such as reduced FURIN mRNA expression in the brains of Alzheimer’s disease patients or schizophrenia patients, has implicated a crucial role of furin in the pathophysiology of neurodegenerative and neuropsychiatric diseases. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 354 publications
0
18
0
Order By: Relevance
“…The 4 genes were ZC3H11A , FURIN , SMARCD3 , and PPP4R2 , and 2 of them were previously reported associated with gray matter volume ( ZC3H11A ) 37 and AD ( FURIN ). 38 These sensitivity analyses supported the association of GPER1 RNA expression in DLPFC with AD phenotypes in women.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The 4 genes were ZC3H11A , FURIN , SMARCD3 , and PPP4R2 , and 2 of them were previously reported associated with gray matter volume ( ZC3H11A ) 37 and AD ( FURIN ). 38 These sensitivity analyses supported the association of GPER1 RNA expression in DLPFC with AD phenotypes in women.…”
Section: Resultsmentioning
confidence: 54%
“…The analyses indicated that 4 genes had the same type of associations that GPER1 had: their RNA expressions were associated with faster cognitive decline and more tau tangles. The 4 genes were ZC3H11A, FURIN, SMARCD3, and PPP4R2, and 2 of them were previously reported associated with gray matter volume (ZC3H11A) 37 and AD (FURIN) 38 . These sensitivity analyses supported the association of GPER1 RNA expression in DLPFC with AD phenotypes in women…”
Section: Sensitivity Analysesmentioning
confidence: 95%
“…Most of the existing furin inhibitors were developed based on furin-substrate peptide analogs, which have good binding to the catalytic pocket of furin but lack chemical and structural diversity [ 18 , 37 ]. Additionally, given the importance of furin in multiple diseases including SARS-CoV-2 infection and tumors, its biochemical studies need to be more advanced [ 7 , 8 , 38 , 39 ]. In the present work, a potential inhibitor of furin with a novel backbone was identified, more importantly, its novel non-competitive allosteric regulatory mode was discovered through enzyme kinetic experiments and structural simulation studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furin is associated with a variety of diseases, such as cardiovascular diseases and endocrine system disorders, and is especially closely related to viral infections and tumors [ 5 , 6 , 7 , 8 ]. With the outbreak of COVID-19 in the last three years, research related to furin-mediated viral infections has been accelerated.…”
Section: Introductionmentioning
confidence: 99%
“…When the total iron content is excessive, the activity of furin decreases, and the activity of β-secretase increases, which enhances the production of the amyloid pathway. In contrast, when iron was deficient, furin activity increased, α-secretase activity increased, and nonamyloid pathway formation was obvious …”
Section: Ferroptosis and Admentioning
confidence: 95%